Respuesta :

Esther

Answer:

[tex]a)\ y=-\frac{1}{3}x[/tex]

Step-by-step explanation:

Slope (m) form: [tex]\frac{y_2-y_1}{x_2-x_1}[/tex]

[tex]m=\frac{y_2-y_1}{x_2-x_1} \\\\m=\frac{1-0}{-3-0} \\\\m=\frac{1}{-3} \\\\m=-\frac{1}{3}[/tex]

[tex]y=mx+b\\y=-\frac{1}{3}x +b[/tex]

(0, 0)

[tex]y=-\frac{1}{3}x +b\\0=-\frac{1}{3}(0) +b\\0=0+b\\0=b[/tex]

[tex]y=-\frac{1}{3}x +0\\y=-\frac{1}{3}x[/tex]

Check your answer:

[tex]y=-\frac{1}{3}x \\1=-\frac{1}{3}(-3)\\1=-1[/tex]

This statement is true

Hope this helps!

Ver imagen Esther